Comparison of adaptive traffic control benefits for recurring and non‐recurring traffic conditions. Issue 3 (27th September 2016) - Stevanovic, Aleksandar; Dakic, Igor; Zlatkovic, Milan
Abstract : When adaptive traffic control systems are deployed in the field, agencies install them for one of two reasons: (i) to cope with day‐to‐day traffic fluctuations and/or (ii) to address frequent but sudden cases with special traffic (incidents, inclement weather etc.). There is an ongoing debate among researchers in which of these two cases adaptive systems are more effective. Yet, no previous studies have examined this issue with enough rigour and attention. This study compares InSync adaptive traffic control system to three conventional time‐of‐day (TOD) signal timing plans in a microsimulation environment to address aforementioned research question. A comprehensive set of scenarios and performance measures has been prepared to evaluate, in microsimulation, operations of an adaptive system InSync on a 12‐intersection corridor along SR‐421 in Volusia County, FL. The Vissim model of SR‐421 was carefully calibrated and validated to resemble the field conditions. The findings show that InSync outperformed the TOD signal timing plans on various spatial levels and its performance made bigger savings in the case of special non‐recurring traffic conditions.